2015
DOI: 10.3389/fmicb.2015.00555
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin gene expression regulated by the light dark cycle, light spectrum and light intensity in the dinoflagellate Prorocentrum

Abstract: The proton pump rhodopsin is widely found in marine bacteria and archaea, where it functions to capture light energy and convert it to ATP. While found in several lineages of dinoflagellates, this gene has not been studied in Prorocentrales species and whether it functionally tunes to light spectra and intensities as in bacteria remains unclear. Here we identified and characterized this gene in the bloom-forming Prorocentrum donghaiense. It is a 7-helix transmembrane polypeptide containing conserved domains an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 46 publications
(74 reference statements)
4
48
0
Order By: Relevance
“…The proton-pump type rhodopsins can create a proton gradient to drive synthesis of ATPase, in lieu of photosynthesis 47,48 . An earlier gene-expression analysis of the bloomforming Prorocentrum donghaiense 49 revealed that proton-pump rhodopsins may compensate for photosynthesis under light-deprived conditions. These rhodopsins were also found to be highly expressed in diatoms under iron-deficient conditions 50 .…”
Section: What Makes Polarella Polarella?mentioning
confidence: 99%
“…The proton-pump type rhodopsins can create a proton gradient to drive synthesis of ATPase, in lieu of photosynthesis 47,48 . An earlier gene-expression analysis of the bloomforming Prorocentrum donghaiense 49 revealed that proton-pump rhodopsins may compensate for photosynthesis under light-deprived conditions. These rhodopsins were also found to be highly expressed in diatoms under iron-deficient conditions 50 .…”
Section: What Makes Polarella Polarella?mentioning
confidence: 99%
“…The authors speculated that proton-pumping rhodopsins could contribute to the acidification of feeding vacuoles in phagotrophic dinoflagellates. Subsequent analyses in the photosynthetic dinoflagellate Prorocentrum donghaiens CCMAXU-364 showed that xanthorhodopsin gene expression is regulated by light and influenced by the light spectrum and intensity (153). Recent work on O. marina CCMP1795 showed that light induces rhodopsin expression and promotes survival under starvation (79), supposedly by providing energy for maintenance of basic cell integrity.…”
Section: Proton-pumping Rhodopsins In Chlorophyll-containing Microbesmentioning
confidence: 99%
“…All known eukaryotic xanthorhodopsins exhibit the DLE motif that characterizes maximum absorption in the green spectrum, as demonstrated for the Prorocentrum donghaiense xanthorhodopsin (Shi et al ., ). Members of the eukaryotic proteorhodopsin clade, conversely, seem to be tuned to blue light (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological function of proton-pumping rhodopsins remains elusive, but includes stimulation of growth (Gomez-Consarnau et al, 2007), enhanced starvation survival (Gomez-Consarnau et al, 2010) and inorganic carbon fixation (Palovaara et al, 2014) in certain bacteria (reviewed in Pinhassi et al, 2016). In marine eukaryotes, proton-pumping rhodopsins have been suggested to provide cellular energy to photoautotrophs under iron (Marchetti et al, 2015) or light (Shi et al, 2015) limitation.…”
Section: Introductionmentioning
confidence: 99%